2017
DOI: 10.1016/j.cma.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

A robust patch coupling method for NURBS-based isogeometric analysis of non-conforming multipatch surfaces

Abstract: A robust patch coupling method for NURBS-based isogeometric analysis of non-conforming multipatch surfaces

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 40 publications
(61 reference statements)
3
45
0
Order By: Relevance
“…Moreover, in [36] the restrictions are enforced by means of a penalty method, whereas the coupling technique presented here employs static condensation. The proposed procedure is explained below; a more detailed study of it can be found in [37].…”
Section: Enforcing Continuity Across Non-conforming Nurbs Patchesmentioning
confidence: 99%
“…Moreover, in [36] the restrictions are enforced by means of a penalty method, whereas the coupling technique presented here employs static condensation. The proposed procedure is explained below; a more detailed study of it can be found in [37].…”
Section: Enforcing Continuity Across Non-conforming Nurbs Patchesmentioning
confidence: 99%
“…γ 1,1 is the sole interface of Ω (1) and it has non-null intersection with just one interface of each one of the other subdomains. Ω (2) has two interfaces: γ 2,1 (that adjacent to Ω (1) ) and γ 2,2 (the top one adjacent to both Ω (3) and Ω (4) ); Ω (3) has three interfaces: γ 3,1 (that adjacent to Ω (4) ), γ 3,2 (that adjacent to Ω (1) ) and γ 3,3 (that adjacent to Ω (2) ); Ω (4) has three interfaces: γ 4,1 (that adjacent to Ω (3) ), γ 4,2 (that adjacent to Ω (1) ) and γ 4,3 (that adjacent to Ω (2) ) In the patch Ω (k) we define a NURBS space N (k) h k as defined in (20) and the corresponding finite dimensional spaces V (k) h k (see (8)) that are totally independent of the discretizations inside the adjacent patches. For each face γ k,α ⊂ Γ k we define the trace space…”
Section: Remark 81mentioning
confidence: 99%
“…In the last years, the treatment of multipatch geometries has been investigated in several papers, far from be exhaustive we mention [10,11,26,37,41,47,8,7,34,30,27,43,6,32,15,29]. In this paper we propose to apply the INTERNODES method to solve elliptic problems within the IgA framework on non-overlapping and non-conforming multipatch configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches are considered, e.g., Nitsche's method [6,7], penalty based methods [8] and mortar methods [9,10], and there is a recent interest in higher-order couplings, see, e.g. [11,12]. A recent practical review, which includes the related issue of trimming, is given in [13].…”
Section: Introductionmentioning
confidence: 99%